Properties of $s\tilde{θ}$-open Sets in Generalized Topological Spaces (European Journal of Pure and Applied Mathematics, 2024)
A study of $\tilde{θ}$-open sets in generalized topological spaces started in 2011 by Min \cite{wkm}. In this paper, we introduce the concepts of $s\tilde{θ}$-open sets, $s\tilde{θ}$-closed sets, $s\tilde{θ}$-continuous functions and $s\tilde{θ}$-irresolute functions on generalized topological spaces. We also study some basic propertiesof such sets and functions.
Keywords: $s\tilde{θ}$-open set, $s\tilde{θ}$-continuous function, $s\tilde{θ}$-irresolute function